Implementasi Metode Socrates Di Era Pendidikan - Baginda Edward Siagian; Tian Abdul Aziz; Lukman El Hakim (Pendidikan Matematika FKIP Universitas Mataram, 2023)
This research discusses the implementation of the Socratic method in modern education. The purpose of this research is to improve the critical thinking skills of eighth grade students when they study the Pythagorean content in mathematics through the use of the Socratic approach. The Socratic technique is one of them. The Socratic dialogue learning strategy is based on the idea that knowledge and higher-order thinking skills can be developed through collaborative question and answer sessions between students and instructors and between students, making use of verbal and non-verbal cues. The results of research conducted at SMAN 15 Bandarlampung show that compared to students who are taught using more conventional methods, students who are exposed to the Socratic approach have a much greater increase in critical thinking skills. More than 75% of students are actively involved in the learning process, and most of those who participate do so effectively. It was found that the Socratic method was effective in eliciting thoughtful responses from the class